Nature's blessing or nature's curse: The political economy of transition in resource-based economies - Akram Esanov; Martin Raiser; Willem Buiter (University of Bonn, Center for Development Research (ZEF), 2004)
This paper analyses the reform progress made in the energy-rich states of the Commonwealth of Independent States (CIS), Azerbaijan, Kazakhstan, Turkmenistan and Uzbekistan (AKTU for short) and contrasts their development to that in the resource-poor countries at the CIS periphery. The main argument of the paper is that far from being a blessing that would have allowed energy-rich countries to cushion the impact of reforms and thus make faster progress, energy rents have often been wasted or appropriated by the ruling elites. Progress in key structural reforms has in some cases lagged even behind other CIS countries and significant policy challenges need to be addressed if natural resource wealth is not to turn into a curse for the region.
Keywords: 330; Political Economy; Resource /Energy Economics and Policy; Übergangswirtschaft; Natürliche Ressourcen; Energiereserven; Rohstoffreichtum; GUS-Staaten; Zentralasien